A STUDY ON THE TEACHING METHOD USED IN TEACHING ENGLISH TO THE FIFTH YEAR STUDENT OF SDN 1 POKOH KIDUL WONOGIRI IN 2007/2008 ACADEMIC YEAR - SAGITANINGSIH, ARIAN (2007)
The objectives of this study are to describe the teaching method used by the English teacher at SDN 1 Pokoh Kidul, Wonogiri, the problem faced by the English teacher, and describe the ways used by the English teacher to overcome the problem. In this research the data are derived from event, and informant. In collecting the data, the researcher uses observation and interview. Based on the research findings, the conclusion can be drawn as follows: (1) the teaching method used by the English teacher namely: Total physical response and Natural Approach; (2) the Problems faced by the teacher in SDN 1 Pokoh Kidul, Wonogiri. The students can't concentrate on the materials if the other class was noisy. The students think that English is not important, they are not confident; (3) To solve the problems, the teacher gives point to make the students active. The teacher also asked the students one by one to answer the question.